Arabic-Romance Medico-Botanical Glossaries in Hebrew Manuscripts from the Iberian Peninsula and Italy. - Bos, Gerrit; Mensching, Guido (Aleph: Historical Studies in Science & Judaism, 2015)
Some late medieval bilingual and multilingual medico-botanical glossaries in Hebrew characters, preserved in the Vatican Library (in particular MSS ebr 356, 361, 365, and 417) are discussed. These lists contain Arabic and (sometimes) Hebrew medico-botanical terms, alongside numerous representatives of the various Romance dialects spoken in the regions where Jewish scholars and physicians lived and worked (the Iberian Peninsula, southern France, and parts of Italy). The main goal is to identify the Romance varieties used in these lists, because they can help indicate the lists' origin and transmission paths.